The Effect of Shareholder Pressure, Board Gender Diversity, Size of the Board of Directors, and Company Age on the Quality of Sustainability Report (Company Study on IDX in the Transportation and Energy Sector in 2019-2023) - Kusuma, Pipit Mike; Muhyarsyah, Muhyarsyah (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study examines the influence of shareholder pressure, board gender diversity, board size, and company age on the quality of sustainability reports using a descriptive quantitative method using panel data regression with Eviews. The results of the study showed that shareholder pressure had no effect on the quality of sustainability reports, board gender diversity, size of the board of directors and the age of the company had a significant effect on the quality of sustainability reports. These findings underscore the need for companies to understand and consistently comply with the standards of corporate activity responsibility that have an impact on the environmental, social, and economic scope which are presented transparently and accessible to stakeholders through quality sustainability.